2008
DOI: 10.1080/02688690801971667
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized 1-year follow-up comparison of bilateral subthalamotomy versus bilateral subthalamic stimulation and the combination of both in Parkinson's disease patients: a pilot study

Abstract: It has been suggested that potential risk of hemiballismus after subthalamotomy makes DBS preferable to ablation for IPD treatment; however, cost and the need for regular electrode control have also been observed as disadvantages to stimulation. The objective was to compare efficacy and safety of different surgical approaches to STN, in a prospective randomized pilot study. Sixteen consecutive IPD patients randomized to receive either: bilateral STN-DBS, bilateral subthalamotomy or unilateral subthalamotomy pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 46 publications
0
36
0
6
Order By: Relevance
“…105,130 In fact, no studies using a cognitive test (mini-mental state examination) observed a decline after unilateral or bilateral lesions. 7,8,25,110,170 Slight improvements in verbal fluency, as well as decreases in dementia, apathy, and depression were seen in patients. 7,8 A recent study demonstrated decreased attention, inhibition, and verbal learning in up to 30% of the patients, but these did not affect patients globally.…”
Section: Cognitive Outcomementioning
confidence: 97%
See 2 more Smart Citations
“…105,130 In fact, no studies using a cognitive test (mini-mental state examination) observed a decline after unilateral or bilateral lesions. 7,8,25,110,170 Slight improvements in verbal fluency, as well as decreases in dementia, apathy, and depression were seen in patients. 7,8 A recent study demonstrated decreased attention, inhibition, and verbal learning in up to 30% of the patients, but these did not affect patients globally.…”
Section: Cognitive Outcomementioning
confidence: 97%
“…Subthalamotomy was not included in the rec- ommended procedures for motor complications because of insufficient evidence. Two studies 41,110 met Level I criteria, depicted by at least 1 high-quality RCT, but these studies were not included in the review because of their small sample sizes. In the first study, 41 unilateral subthalamotomy was compared with unilateral pallidotomy and bilateral STN DBS.…”
Section: Subthalamotomy Versus Other Surgical Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both STN-and GPi-DBS can have non-motor side effects, especially affecting verbal fluency, cognition and mood (Kumar et al, 1999a, b;Dujardin et al, 2001;Schupbach et al, 2005;Smeding et al, 2005Smeding et al, , 2006Smeding et al, , 2011Castelli et al, 2006;De Gaspari et al, 2006, Merello et al, 2008. Verbal fluency and cognition problems are more often seen in old patients (Hariz et al, 2000;Saint-Cyr et al, 2000;Funkiewiez et al, 2004;Smeding et al, 2011), or in those with poor cognition or depression at baseline (De Gaspari et al, 2006).…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
“…Since then, although a very effective procedure, just a few groups around the world have incorporated this technique in their armamentarium for the treatment of Parkinson's disease [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16]. The main reason for that is the fear of producing operation-induced dyskinesia (OID) such as hemiballism and chorea [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19]. In the present study, we try to establish the factors involved in the genesis of OID, which happened in 6 out of 54 patients (11%) submitted to unilateral subthalamotomy in our institutions.…”
Section: Introductionmentioning
confidence: 99%